A Plumieridine-Rich Fraction From Allamanda polyantha Inhibits Chitinolytic Activity and Exhibits Antifungal Properties Against Cryptococcus neoformans - Silva e Souza, Eden; Barcellos, Vanessa de Abreu; Sbaraini, Nicolau; Reuwsaat, Júlia Catarina Vieira; Schneider, Rafael de Oliveira; da Silva, Adriana Corrêa; Garcia, Ane Wichine Acosta; von Poser, Gilsane Lino; Barbosa, Euzébio Guimarães; Lima, João Paulo Matos Santos; Vainstein, Marilene Henning (Frontiers in Microbiology, 2020)
Cryptococcosis is a fungal infection caused mainly by the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii. The infection initiates with the inhalation of propagules that are then deposited in the lungs. If not properly treated, cryptococci cells can disseminate and reach the central nervous system. The current recommended treatment for cryptococcosis employs a three-stage regimen, with the administration of amphotericin B, flucytosine and fluconazole. Although effective, these drugs are often unavailable worldwide, can lead to resistance development, and may display toxic effects on the patients. Thus, new drugs for cryptococcosis treatment are needed. Recently, an iridoid named plumieridine was found in Allamanda polyantha seed extract; it exhibited antifungal activity against C. neoformans with a MIC of 250 µg/mL. To address the mode of action of plumieridine, several in silico and in vitro experiments were performed. Through a ligand-based a virtual screening approach, chitinases were identified as potential targets. Confirmatory in vitro assays showed that C. neoformans cell-free supernatant incubated with plumieridine displayed reduced chitinase activity, while chitinolytic activity was not inhibited in the insoluble cell fraction. Additionally, confocal microscopy revealed changes in the distribution of chitooligomers in the cryptococcal cell wall, from a polarized to a diffuse cell pattern state. Remarkably, further assays have shown that plumieridine can also inhibit the chitinolytic activity from the supernatant and cell-free extracts of bacteria, insect and mouse-derived macrophage cells (J774.A1). Together, our results suggest that plumieridine can be a broad-spectrum chitinase inhibitor.